The Argentine continental shelf: morphology, sediments, processes and evolution since the Last Glacial Maximum - Violante, Roberto Antonio (2014)
The Argentine continental shelf is one of the largest and smoothest siliciclastic shelves in the world. Although it is largely emplaced in a passive continental margin, the southernmost regions are related to transcurrent and active margins respectively associated with the Malvinas Plateau and Scotia Arc. Sea-level fluctuations, sediment dynamics and climatic/oceanographic processes were the most important conditioning factors in the modelling of the shelf, with a minor influence from isostatic and tectonic factors that are more relevant in the southernmost regions. The shelf is shaped by diverse geomorphic features, among which the most significant are four sets of terraces genetically associated to sea-level stillstands during the post-glacial transgression; the final one occurred at around 11 ka and is associated with the Younger Dryas event. The Last Glacial Maximum (LGM) sedimentary sequence is composed of, on average, 5–15 m-thick terrigenous, siliciclastic, relict–palimpsest sands mainly sourced from the Andean region, with minor amounts of bioclast and gravels, resulting from the reworking of pre-transgressive coastal environments.